Navigating Leadership and Identity: A Qualitative Exploration of Class Monitor Roles among Vietnamese English-Major Students - Thanh Thao Le; Dinh Phan Nguyen; Thanh Vy Ho; Thanh Hieu Vy Nguyen; Thi Kim Tho To (FOSTER: Journal of English Language Teaching, 2024)
This qualitative study delves into the impacts of taking on the role of a class monitor among Vietnamese English-major students, focusing on the nuanced experiences and growth trajectories stemming from this leadership position. Conducted within two higher education institutions in the Mekong Delta, the research employed semi-structured interviews to capture the voices and narratives of 15 participants. Grounded in the Constructivist Grounded Theory and the Phenomenological Approach, the study unearthed several pivotal themes. These included feelings of empowerment through leadership responsibilities, the intricate balancing act of cultural mediation and dual identities, enhancement of English communication skills, the evolution of prioritization skills, profound introspective journeys towards self-realization, and a deep-seated desire to inspire and create a lasting legacy. The findings not only shed light on the multifaceted impacts of the class monitor role but also underscore the transformative potential of such positions in fostering personal and academic growth. The study contributes uniquely to the discourse on student leadership, offering educators, policymakers, and institutions a deeper understanding of the experiences and challenges faced by student leaders in a Vietnamese context. It emphasizes the importance of recognizing and harnessing the profound personal and collective journeys these roles can initiate.